Obstacles and efforts to overcome them in protecting children's rights against violence in elementary schools in the Sleman district - Hartini, Sri; Hanum, Fathikah Fauziah; Priyanto, Anang (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
The aims of this research are: to identify obstacles in protecting children's rights against violence in elementary schools in Sleman Regency and to describe efforts to overcome obstacles in protecting children's rights against violence in elementary schools in Sleman Regency. This research is a descriptive qualitative research approach. The research subjects were four school principals, three teachers and two education staff. Data collection techniques with interviews and documentation. The technique of checking the validity of the data is done by using cross check data. Inductive data analysis which includes data reduction, categorization and unitization of data, presentation of data and drawing conclusions. The results of the research show that in carrying out these protection efforts the school revealed that there were several obstacles faced. These obstacles come from within (internal) and from outside the school (external). Internal barriers in the form of the lack of the role of educational staff or employees and parents who are less open. While external obstacles such as violence occur outside the school which causes ignorance on the part of the school. schools make efforts to overcome internal and external obstacles in prevention efforts by creating child-friendly school programs and recruiting Counseling Guidance teachers.